4‐2: Student Paper: High‐Performance, Coplanar Polycrystalline InGaO Thin‐Film Transistor for Large‐Area, High‐Resolution AMOLED Display. Issue 1 (28th June 2022) - Rabbi, Md. Hasnat; Lee, Suhui; Sasaki, Daich; Kawashima, Emi; Tsuruma, Yuki; Jang, Jin
Abstract : We report a very simple hotplate crystallization technique to achieve the polycrystalline InGaO (IGO) thin films at low temperature (<400 °C). The coplanar thin film transistor (TFT) with polycrystalline IGO exhibits linear mobility over 50 cm 2 V −1 s −1 and excellent stability under PBTSINBTS and 85% humidity at 85°C for 2 days. We have also achieved very fast 23 stage ring oscillator with a frequency of 2.36 MHz because of coplanar structure and high mobility. This low‐cost technique is very suitable for the manufacturing of polycrystalline oxide TFT backplane for large area, high resolution AMOLED displays.